The Factors Affecting Indonesian Banking Companies' Audit Report Lag - Putu Kepramareni; Sagung Oka Pradnyawati; Anak Agung Adde Leony Devi (Universitas Warmadewa, 2025)
The main objective of this article is to identify the occurrence of audit report lag by examining several financial ratios, auditors and firm size. All research data were obtained by accessing the annual reports of banking companies in the capital market. Data were collected, processed and analyzed with the help of software using logistic regression tests. Based on the tests carried out, it can be explained that audit report lag can be minimized by increasing or improving the company's profitability, where the test shows a negative influence between profitability and audit report lag. For solvency testing, the audit committee, auditor reputation and firm size do not show a significant influence on the occurrence of audit report lag.